Passive Smoking and Its Correlation with Stunting in Children: A Systematic Review - Rahmiwati, Anita; Karlinda, Karlinda; Hasyim, Hamzah; Febriyansyah, Febriyansyah (UI Scholars Hub, 2024)
Passive smoking is a significant risk factor for stunting in children, highlighting the urgent need for effective public health measures. This study aimed to investigate the association between passive smoking and stunting in children aged 0 months-7 years. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive literature search was conducted across multiple online databases, including PubMed, ProQuest, Science Direct, Willey Online Library, Sage Journal, Cambridge University Press, and Oxford Academic. The quality of included articles reporting observational studies was assessed using the Critical Appraisal Skill Programme (CASP) checklist, presenting data through narrative synthesis. Findings suggested that passive smoking significantly contributed to the risk of stunting in children. Most reviewed articles were from low-income countries and reported studies with various age groups, demographic characteristics, and self-reported measures. Establishing a causal relationship remains challenging, with 99% of these studies using a cross-sectional design. Based on these findings, further study into this relationship using more comprehensive study designs is necessary. Interventions for mothers and children experiencing stunting should also be prioritized to reduce risk factors and strengthen protective factors.